Identify the second step in solving this equation for y: −3(y + 6) = 21. (1 point)

Responses

Add 6 to both sides.
Add 6 to both sides.

Divide both sides by −3.
Divide both sides by negative 3.

Divide both sides by 6.
Divide both sides by 6.

Subtract 6 from both sides.

1 answer

To solve the equation \(-3(y + 6) = 21\), the first step is to divide both sides by \(-3\) to isolate the term containing \(y\). The second step, after dividing, would involve simplifying the equation.

So, the correct second step is:

Divide both sides by −3.

Similar Questions
  1. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
  2. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 1 answer
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions